Handle with care - Harte, Marie (Harte, Marie. Veteran movers, 2019)
"Evan Griffith has had many careers in his life. But who knew working for his family's moving company would hold just as much action as his stint in the Marine Corps? On an unforgettable job, Evan finds himself taken by a teenage conman and confronted by a woman wielding a knife - and promptly falls head over heels for her. Kenzie Sykes is doing her best to raise her little brother and keep him out of jail - all while dealing with her own broken heart that just hasn't healed. She doesn't have time for romance. He's not asking... Until he is, and she finds herself saying yes" --